Density of statically deposited bed - Zawawi Samba Mohamed,; Mahbubur Rahman,; Jamal Mohd Amin, (1996)
Variation of density for statically deposited cohesive sediment bed was investigated under the effect of salinity and consolidation period. The density of natural mud and kaolinite bed was found to increase with depth. This was due to the variation in initial suspension concentration and overburden. Salinity is found to have little effect on bed density, while consolidation causes the bed density to increase with depth. Overall density for kaolinite is higher than natural mud. The density profile for seven test beds is nearly S shape